Woman Creativepreneurship Based on Minangkabau Culture - Sari, Fitria; Sapriya, Sapriya; Supriatna , Nana; Mulyadi, Hari; Hasanuddin, Hasanuddin (Masyarakat Linguistik Indonesia Universitas Andalas, 2024)
Indonesia comprises various ethnic cultures, which has its own uniqueness. One element of culture is a livelihood system. The Minangkabau ethnic community has a uniqueness that is represented by the tradition of migrating and the livelihood system of trading. Migrants were initially only carried out by men but later were also joined by women. Many Minangkabau women migrants are successful in their overseas and trading businesses. This prompted this research to be carried out with the title Minangkabau Woman Creativepreneurship. This paper applies qualitative approach, with ethnographic research methods and an anthropolinguistic paradigm. The informants in this research were 10 Minangkabau women who were creative in running their businesses. The location of this research is Dharmasraya Regency, West Sumatra Province. This research found 7 (seven) Minangkabau Woman Creativepreneurship values, namely: (1) religiosity, (2) hard work, (3) discipline, (4) honesty, (5) never giving up, (6) thriftiness, and (7) creativity. These values were internalized from the teachings of the Minangkabau adat. It is deemed that cultural values are represented in and internalized from language in the form of adages, forming attitudes, character, ethos and ethics and behavior, leading to their success. These findings are relevant to the current state of unemployment rates and in motivating local cultural education in the education system.